Трагизм Homo Faber и надежды Homo Humanus - Мищенко, Виктор Иванович (Харківський національний університет ім. В. Н. Каразіна, 2019)
В статье рассматривается роль человека труда Homo Faber в развитии цивилизации, становлении самого человека, как мыслящего существа (Homo sapiens). Констатируется факт глубокого кризиса Homo Faber, зафикстрованного в художественной литературе и философских исследованиях. Анализируются попытки представителей «школы человеческих отношений» активизировать мотивацию и творческую деятельность Homo Faber. Выявляются факторы современного производства, способствующие разрушению духовности личности и деградации Homo Faber. Рассматриваются возможности его духовного развития, заключённые в модели Homo Humanus, дающего надежды Homo Faber на лучшую судьбу. Исследуются возможные варианты развития Homo Faber: использование ресурсов саморазвития личности, адаптация человека к цивилизованным тектоническим сдвигам, а так же вариант управления эволюции человека. Стратегия эволюционных изменений включает в себя: цель – формирование Homo Spiritus (человека духовного), как высшей формы Homo Humanus. Она определяет выбор средств управленческого воздействия – использования мощного арсенала образования, науки и современной техники, позволяющей существенного расширить исследование космоса, микромира, сознания и, получив инновационные знания о мире, вызвать катарсические процессы в душе человека, сформировать стремление к духовному восхождению.

The article discusses the role of Homo Faber’s human labor in the development of civilization, the development of a human himself as a thinking being (Homo sapiens). The fact of the deep crisis of Homo Faber, fixed in fiction and philosophical studies, is stated. The attempts of representatives of the “school of human relations” to intensify the motivation and creative activity of Homo Faber are analyzed. The factors of modern production that contribute to the destruction of the spirituality of the individual and the degradation of Homo Faber are revealed. The possibilities of his spiritual development, concluded in the model of Homo Humanus, giving hope to Homo Faber for a better destiny, are considered. Possible ways of development of Homo Faber are explored: the use of personality self-development resources, human adaptation to civilized tectonic shifts, as well as the variant of managing human evolution. The strategy of evolutionary change includes: the goal that is to form Homo Spiritus (spiritual man), as the highest form of Homo Humanus. It determines the choice of means of managerial influence - using a powerful arsenal of education, science and modern technology, allowing significant expansion of space exploration, the microworld, consciousness and, having received innovative knowledge about the world, to cause cathartic processes in the human soul, to form the desire for spiritual ascent. The process of influencing on human consciousness is planned to be carried out taking into account the main stages of spiritual self-development definition. Thus, at the stage of a person formation – to bring up spiritual qualities (curiosity, cordiality and diligence), at the stage of personality formation - spiritual (openness to the world, intelligence and creativity). At the stage of self-assertion in life, to achieve the integration of the processes of increasing the plasticity of a personality, as an ability to manifest a state of spirituality in various spheres of being, and spiritual concentration, as the depth of the world perception. At the stage of self-realization of the personality, to support the desire for transcendence and the fullness of self-expression. Using the principles of the concept of continuous development and relying on the arsenal of the possibilities of the lifelong concept of lifelong education affirmed in society, to counteract the spiritual degradation of the individual. Aiming to intensify aspirations in spiritual self-development, the author suggests studying the academic discipline “Fundamentals of Human Evolution”, the content of which consists of interrelated sections, each of which is intended to ensure the emergence of a certain modification of the spiritual image of the personality: Homo wondering (person surprising, revealed to the world), Intelligent Populous (person of intelligent), organically combining Homo Cogitate (a person capable of deep reflective critical thinking) and Homo Responsible (a person in charge), Homo Inspired (human inspired to create), creating together the image of a human of spiritual noospheric future – Homo Spiritus.
Tragism of Homo Faber and hopes of Homo Humanus
Keywords: эволюция человека; управление; духовное развитие; личность; духовный облик; managing human evolution; spiritual development; spiritual face of personality